Fans, Co-creation and the Social Media - the Case of 'Tibi atya' - Glózer, Rita (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER By presenting a brief empirical analysis the main aim of this paper is to reveal new online-offline dynamics of fan communities in the social media. Apparently, there are yet unexploited opportunities in the integration of scientific approaches of media studies and consumer behaviour research, especially regarding the participation of brand fans in the value creation process. Adopting a complex multidisciplinary approach a current case of the collaborative online media produsage was examined as a manifestation of media fandom on one hand, and a precedent of the co-creation on the other hand. METHODOLOGY Inasmuch as the previous phenomenon can be elaborated by explaining symptomatic examples, the qualitative inquiry and the case study method were used. In the course of the investigation multiple sources of evidence were applied such as related blogs and social media sites, the web-shop, the official homepage and the book of the initiators, and some articles discussing the investigated phenomenon in the mainstream online media and public blogs. MOST IMPORTANT RESULTS The study unfolds in great detail the course of the ‘Tibi atya’ case where a fictitious character was created and by humorous content promoted on social media sites. Creators fostered the shaping of an extensive fan community in a short time and founded a start-up and by selling other branded products and services they started to extend their agency to offline spaces as well. The ‘Tibi atya’ case brings to light that online communities based merely on enjoyment of media content can be extended to offline places as well, while their media consumption could be expanded and transformed into product or service consumption as well. RECOMMENDATIONS To utilize potentials of co-creation leaders need more detailed insight in the current functioning of online fan communities. Providing intense qualitative analyses the media and cultural studies might support and inspire these efforts.